Assessment of peripheral blood concentration of angiopoietin 1, angiopoietin 2 and Tie-2 (a tyrosine kinase receptor) of patients with goitre treated surgically - Joanna Kalupa; Krzysztof Kuzdak; Krzysztof Kołomecki (Videosurgery and Other Miniinvasive Techniques)
Introduction: Blood vessel formation by angiogenesis is essential for goitre development. Angiopoietin 1 (Ang-1),angiopoietin 2 (Ang-2) and Tie-2 receptor (rTie-2) are involved in part of angiogenesis. Ang-1 and rTie-2 expressionincreases in goitre.Aim: To determine serum concentrations (SC) of angiogenic cytokines of patients with goitre treated surgically.Material and mathods: Thirty-six patients with goitre aged 29-64 were examined. They were divided into groups: nontoxicnodular goitre (NTNG) and toxic goitre (TG). Each group was divided into subgroups: before and after surgery.The control group comprised 10 healthy subjects. Ang-1, Ang-2 and rTie-2 SC were measured in euthyroid subjects byELISA. Measurements were performed before the procedure and three months after.Results: Before surgery Ang-1 median (Me) SC in patients with TG was higher than in patients with NTNG (109 368pg/ml vs. 71 185 pg/ml) and in controls (109 368 pg/ml vs. 57 815 pg/ml). Ang-1 Me in TG patients was higher prior tothan after surgery (109 368 pg/ml vs. 65380 pg/ml). Ang-2 Me in TG patients was higher after than prior to surgery(4055 pg/ml vs. 3924 pg/ml). Significant correlations were found between Ang-1 and Tie-2 Me (r = 0.53) and Ang-2and Tie-2 (r = 0.58) in patients with NTNG before surgery and between Me Ang-2 and Tie-2 in patients with NTNGafter surgery (r = 0.89) and in controls (r = 0.77).Conclusions: Before surgery in patients with TG SC of Ang-1 was higher than in patients with NTNG and in controls.After surgery in patients with TG SC of Ang-1 decreased, and SC of Ang-2 increased. Significant correlations werefound between SC of Ang-2 and Tie-2 in patients with NTNG and in controls.